Albumin Infusion is not Beneficial in Hypoalbuminemic End-Stage Cancer Patients: A Matched-Pair Analysis - Buyukcelik, Abdullah; Demirkazik, Ahmet; Yalcin, Bulent; Dogan, Mutlu; Kavgaci, Halil; Coban, Sahin; Icli, Fikri (AKAD DOKTORLAR YAYINEVI, 2012)
In this retrospective study, it was aimed whether albumin infusion is benefical or not in terminally ill hospitalized hypoalbuminemic cancer patients. Between March 2000 and 31 March 2003, the medical records of 27 terminally ill hypoalbuminemic cancer patients who had albumin infusion(Albumin receiving group-ARG), were retrospectively analysed. This grup was matched (1:1) with 27 terminally ill cancer patients who had no albumin infusion (Albumin not receiving group-ANRG), according to age, sex, ECOG PS, diagnosis and the number of metastatic sites. ARG was compared with ANRG, in regard to the changes of pulse rate, blood pressure, in the levels of serum BUN, creatinin, sodium, total protein, and albumin before albumin infusion and 48 hours after albumin infusion, and documented and/or clinical infections after albumin infusion, hospitalization duration, the rate of exitus in hospital and overall survival. There was no difference in patient characteristics between two groups. Likewise, the groups were not different from each other in terms of the changes of pulse rate, blood pressure, in the levels of serum BUN, creatinin, sodium, and documented and/or clinical infections after albumin infusion (p> 0.05). There was a significant increase in the levels of serum total protein and albumin in ARG (p< 0.05). The rate of exitus in hospital is not different between two groups. The median duration of hospitalization was longer in ANRG (p= 0.022). The overall survival was significantly better in ANRG (p= 0.018). Albumin infusion is not benefical in terminally ill hypoalbuminemic cancer patients. Furthermore, it was found that the survival was significantly worse in patients receiving albumin.
Keywords: Cancer; Hypoalbuminemia; Terminally ill cancer patient; Albumin infusion